Paediatric CSF acylcarnitine reference ranges - Plaatjie, Ontefetse Neo; Tutu Van Furth, A. Marceline; Solomons, Regan; Van Der Kuip, Martijn; Mason, Shayne (Frontiers in Molecular Biosciences, 2025)
Acylcarnitines play a crucial role in energy metabolism pathways, primarily known for their involvement in the beta oxidation of fatty acids. However, their roles extend beyond mitochondrial transport; they also contribute to the synthesis of lipids in the brain. The alteration of both plasma and cerebrospinal fluid (CSF) acylcarnitine levels has been reported in various central nervous system (CNS) disorders. However, existing CSF acylcarnitine analysis has primarily focused on adults, highlighting a critical gap in paediatrics, and plasma may not fully reflect CNS-specific metabolic changes. This study aimed to establish reference ranges of CSF acylcarnitine concentrations in paediatric patients. Using LC-MS/MS, we profiled CSF acylcarnitines in 57 non-meningitis children. The acylcarnitine concentrations reported in this study range from 0.01 µM to 4.21 µM. These findings provide a critical reference for future research exploring the role of acylcarnitines in paediatric CNS disorders, bridging a significant gap in the current understanding of acylcarnitine metabolism in children.